AN OVERVIEW OF CONTACT DERMATITIS RELATED TO OCCUPATIONAL CAUSES IN RECENT YEARS - Ziv Leng Nee; Fong Yuke Tien; Pannu Navreet Kaur; Dr Claire Hui Hsien Quah, (The Malaysian Journal of Nursing (MJN), 2013)
Occupational skin diseases, including allergic contact dermatitis and irritant contact dem1atitis, have been commonly reported across various types of occupations. Although the reporting of these symptoms have been long-associated with occupational related causes, many studies have nonetheless continued to report regarding the occupational risk exposures and their resulting cases of contact dermatitis, the existence of which, have well-continued until recent years. Healthcare workers, pharmaceutical industry workers and construction workers collectively suffer from contact dermatitis due to their risks of occupational exposures, either through means of allergic contacts, chemical irritants, or photo allergic exposures. Early diagnosis for occupational related contact dermatitis could contribute towards a better prognosis. A delay in the medical consultation could likely prolong the deterioration of existing symptoms, and henceforth a poorer recovery outcome. It is therefore essential to recognize the needs for early diagnosis and improve medical service access with regards to such occupational risk exposures.